EFFECTIVENESS OF COUNSELLING SERVICES IN REDUCING ACADEMIC STRESS, AND PROMOTING CRITICAL THINKING AMONG JUNIOR SECONDARY SCHOOL STUDENTS IN ANAMBRA STATE - Enwere, Chinwe Augustina; Mbakwe, Uchenna Fidelia (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2025)
Academic stress is a prevalent challenge among junior secondary school students, often affecting their cognitive abilities and overall academic performance. Consequently, this study examined the effectiveness of counselling services in reducing academic stress and promoting critical thinking among junior secondary school students in Anambra State. A descriptive survey design was adopted, and data were collected from 72 respondents, comprising junior secondary school teachers and school counsellors who interact with students and provide counselling support. A structured questionnaire served as the instrument for data collection, ensuring comprehensive insight into the role of counselling services. Experts in the field validated the instrument, and its reliability was established using Cronbach’s alpha. Data were analyzed using descriptive statistics and regression analysis to test the hypotheses at a 0.05 level of significance. The findings revealed that counselling services significantly reduce academic stress and enhance critical thinking skills among students. The study underscores the necessity of strengthening counselling services within schools to support students' academic and personal development. It recommends that policymakers and school administrators integrate more structured counselling interventions to foster resilience and cognitive skills among students.